Knowledge, attitudes and behaviors concerning sun protection/skin cancer among adults in Turkey - (:unkn) unknown (My University, 2009)
Objective: To document the level of knowledge, attitudes and behaviors of adults concerning sun protection and skin cancer. Methodology: This was designed as descriptive and correlational study. The study group comprised of 1020 adults aged 18 to 75, chosen from all seven geographical regions in Turkey. Results: Participants living in East and Southeast Anatolia regions had statistically less knowledge concerning sun protection and skin cancer. The knowledge scores of women were higher than men. The knowledge scores of those in younger age group, students and university graduates were higher than others. Women were sunbathing more often than men to have a darker skin and also were taking more protective measures against skin cancer. Conclusion: Education level, gender and living in a coastal region effect level of knowledge, attitude and behavior about sun protection/skin cancer.
Keywords: Attitude; Behavior; Knowledge; Skin neoplasm